Development of mathematical model and computer program for primary design of transonic axial compressor - A. I. Borovkov; Yu. B. Galerkin; O. A. Solovieva; A. A. Drozdov; A. F. Rekstin; V. B. Semenovsky; P. N. Brodnev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The mathematical model underlying the program for calculating and designing axial compressors is presented. The process of calculating the pressure loss in the elements of the axial compressor stage flow path is described. The loss coefficient consists of losses on the limiting surfaces, secondary losses and profile losses. The effect of roughness on the pressure loss is taken into account by introducing the corresponding empirical coefficient. An algorithm for calculating the blades and vanes angles of the impeller and the guide apparatus is presented by calculating the incidence angle and the lag angle of the flow. The flow lag angle is the sum of the lag angle of the flow on the profile and the lag angle due to viscous flow on the limiting surfaces